2019
DOI: 10.1038/s41598-019-50898-3
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PD-1/PD-L1 in primary breast tumours and metastatic axillary lymph nodes and its correlation with clinicopathological parameters

Abstract: The aim of this study was to compare the expression of PD-1/PD-L1 in primary breast tumours to that in metastatic axillary lymph nodes and to determine the correlation between the PD-1/PD-L1 status and clinicopathologic characteristics. In total, 47 paired breast tumour and metastatic axillary lymph node samples were collected in this study. Immunohistochemical technology was used to determine the positivity or negativity of PD-1/PD-L1. Other patient information was retrieved from medical records. Significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(45 citation statements)
references
References 31 publications
1
44
0
Order By: Relevance
“…These preliminary results justified closer examination of this pathway and its potential therapeutic role in CSCC. Some studies demonstrated the presence of cell surface PD-1/PD-L1 in human tumors, and this expression has been linked to poor clinical outcomes in a variety of cancers [112][113][114][115][116], including CSCC [117,118]. CSCC has the highest mutational burden of all tumors, and is a good candidate for immunotherapy treatment [21].…”
Section: Immunotherapy In Csccmentioning
confidence: 99%
“…These preliminary results justified closer examination of this pathway and its potential therapeutic role in CSCC. Some studies demonstrated the presence of cell surface PD-1/PD-L1 in human tumors, and this expression has been linked to poor clinical outcomes in a variety of cancers [112][113][114][115][116], including CSCC [117,118]. CSCC has the highest mutational burden of all tumors, and is a good candidate for immunotherapy treatment [21].…”
Section: Immunotherapy In Csccmentioning
confidence: 99%
“…Up to 30.7% of PD-1 expression on tumor-infiltrating lymphocytes (TILs) around HER2 + BC is also seen. PD-1/PD-L1 expression in metastatic tumors was correlated with poor prognosis, whereas no relation to clinicopathological features was noted in primary tumors [109]. In essence, it can be seen from literature that high PD-L1 expression combined with an increase in T regulatory cells (Tregs) and a decrease of TILs are associated with poor survival [22,102,107,110].…”
Section: Pd-1/pd-l1 and Her2 Crosstalk In Breast Cancermentioning
confidence: 99%
“…It is known that tumor cells express programmed death-ligand 1 (PD-L1) that binds PD-1 on T cell, resulting in dysfunction of cytotoxic T-cell activity [45]. Several other studies have also shown that microglia expresses PD-L1, which interacts with T cell PD-1 to suppress adaptive immune function and tumor in ltration of T cells [45][46][47]. We therefore examined whether E2 affects PD-L1 expression in microglia.…”
Section: Estrogen Suppressed Anti-tumor Immune Function Of Microgliamentioning
confidence: 99%